Emerging Roles of SPINK1 in Cancer. (6th January 2020) - Räsänen, Kati; Itkonen, Outi; Koistinen, Hannu; Stenman, Ulf-Håkan
Abstract: BACKGROUND: Tumor-associated trypsin inhibitor (TATI) was originally isolated from the urine of a patient with ovarian cancer. It was later shown to be produced by many other tumors and several normal tissues. It had earlier been isolated from the pancreas and was hence called pancreatic secretory trypsin inhibitor (PSTI). It belongs to a family of protease inhibitors presently called serine peptidase inhibitor Kazal type (SPINK). In the SPINK family TATI/PSTI is SPINK1, which is the name used in this review. CONTENT: In addition to being a protease inhibitor, SPINK1 also acts as an acute-phase reactant and a growth factor. Furthermore, it has been shown to modulate apoptosis. Overexpression of SPINK1 predicts an unfavorable outcome in several cancers and determination of SPINK1 in serum can be used to identify patients at increased risk of aggressive disease. Thus serum SPINK1 can be used as a prognostic tumor marker. Because SPINK1 acts as a growth factor and an inhibitor of apoptosis in some cancers, it has also been suggested that it can be a therapeutic target in cancer. However, because SPINK1 is the major physiological inhibitor of trypsin, inhibition of SPINK1 may increase the risk of pancreatitis. SUMMARY: Taking into account the many functions of SPINK1, assessing the role of SPINK1 in cancer has several potentially important clinical applications ranging from a biomarker to a potential new target for cancer therapy.